2021
DOI: 10.1111/aas.13997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID‐19 pandemic at a major Danish trauma center in 2020 compared with 2018–2019: A retrospective cohort study

Abstract: Background The COVID‐19 pandemic demanded changes in societal behavior and health care worldwide. Previous studies have compared trauma patient admissions in COVID‐19‐related lockdowns to prior years. This study describes the COVID‐19 impact on trauma patient admissions during entire 2020 at a major trauma center in Denmark. Methods We retrospectively analyzed trauma patients received by a trauma team and admitted at Aarhus University Hospital in 2020 compared with 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Due to the effect of these restrictions, the number of pedestrians and vehicles on the road decreased. Similar effects were observed globally [ 8 , 9 , 11 , 28 ]. The expected effect of the reduction in traffic was a reduction in traffic and vehicle-related accidents.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Due to the effect of these restrictions, the number of pedestrians and vehicles on the road decreased. Similar effects were observed globally [ 8 , 9 , 11 , 28 ]. The expected effect of the reduction in traffic was a reduction in traffic and vehicle-related accidents.…”
Section: Discussionsupporting
confidence: 83%
“…The expected effect of the reduction in traffic was a reduction in traffic and vehicle-related accidents. In some countries, such as the USA, Australia, England, Spain, and Denmark, it was observed that traffic accidents decreased in line with this expectation [ 8 , 9 , 11 ]. By contrast, Hakkenbrak et al reported an increased number of traffic-related accidents in the Netherlands; this may be because there was no stay-at-home order or curfew in the Netherlands [ 29 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the increasingly stringent measures of containment and the sense of civic responsibility of the population may have played a relevant role in reducing the utilization of EMS especially in the context of an overabundance of information-the so-called infodemic [27]-and conflicting messages from local and national authorities [7,9]. Lastly, restriction measures played a direct role in reducing risk factors-such as road traffic accidents, falls and injuries and air-borne infectious diseases-for the incidence of several acute conditions usually treated in the EMS context; this is confirmed by the fact that injuries and fractures were among the causes of admissions that showed the largest decline in our study [8,[28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 68%
“…The results showed a decrease in the rates of road, work, and leisure accidents and an increase in domestic accidents and undefined “aggressions.” The increase in “aggressions” was not statistically significant. Data from a single hospital in Denmark show no difference in risk ratio for violence comparing the number of patients admitted in 2020 with the average of the previous 2 years (Trier et al, 2022 ). An increase in the incidence of minor injuries was found but there was no change in the severe injuries when not distinguishing the cause and reduction in traffic‐related injuries.…”
Section: Introductionmentioning
confidence: 99%